Numerical computation of dusty hybrid nanofluid flow and heat transfer over a deformable sheet with slip effect - Anuar, Nur Syazana; Bachok, Norfifah; Pop, Ioan (MDPI, 2021)
The mathematical modeling of dusty Cu-Al2O3/water nanofluid flow driven by a permeable deformable sheet was explored numerically. Rather than no–slip conditions at the boundary, velocity slip and thermal slip were considered. To achieve the system of nonlinear ordinary differential equations (ODEs), we employed some appropriate transformations and solved them numerically using MATLAB software (built–in solver called bvp4c). The influences of relevant parameters on fluid flow and heat transfer characteristics are discussed and presented in graphs. The findings showed that double solutions appeared in the case of stretching and shrinking sheets which contributed to the analysis of stability. The stability analysis, therefore, confirmed that merely the first solution was a stable solution. The addition of nanometer-sized particles (Cu) was found to significantly strengthen the heat transfer rate of the dusty nanofluid. Meanwhile, an upsurge in the velocity and thermal slip was shown to decrease the local Nusselt number. The result also revealed that an increment of fluid particle interaction decreased the boundary layer thickness.